2014
DOI: 10.2174/0929867321666131228204839
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin – A New Target for Treating Stroke at the Crossroad of Coagulation and Inflammation

Abstract: Thrombomodulin (TM) is a membrane protein mainly expressed by endothelial cells. It is part of the anticoagulant protein C system but recently several effects were discovered which occur independently of protein C activation. TM binds thrombin and promotes the cleavage of protein C and the thrombin activatable fibrinolysis inhibitor (TAFI), thereby inhibiting coagulation and fibrinolysis. Additionally, it interferes with inflammation, stabilizes barrier function, and increases blood flow under pathological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Protein C interacts with the thrombin-TM complex and the endothelial protein C receptor (EPCR), transforming into activated protein C, which may inactivate factors Va and VIIIa with protein S assistance (13). TM is a membrane protein expressed by endothelial cells, including in arteries, veins, capillaries and lymphatic vessels, and in other cell types, including astrocytes, keratinocytes and neutrophils (14). Previous studies verified that TM was part of the anticoagulant protein C system; however it has become clear that, in addition, TM provides anti-inflammatory protection independently of activated protein C, with or without activation of thrombin-activated fibrinolysis inhibitor (15).…”
Section: Discussionmentioning
confidence: 99%
“…Protein C interacts with the thrombin-TM complex and the endothelial protein C receptor (EPCR), transforming into activated protein C, which may inactivate factors Va and VIIIa with protein S assistance (13). TM is a membrane protein expressed by endothelial cells, including in arteries, veins, capillaries and lymphatic vessels, and in other cell types, including astrocytes, keratinocytes and neutrophils (14). Previous studies verified that TM was part of the anticoagulant protein C system; however it has become clear that, in addition, TM provides anti-inflammatory protection independently of activated protein C, with or without activation of thrombin-activated fibrinolysis inhibitor (15).…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be associated with the loss of anti-inflammatory caused by low levels of circulating activated protein C (APC) that have been assessed in stroke patients (Macko et al, 1996;Wang et al, 2013;Wenzel et al, 2014). Lower circulating APC levels have also been linked to inflammatory status in both stroke and controls (Macko et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed the expression of TM within the cerebrovascular endothelium, where its anti-coagulant and antiinflammatory properties are thought to be critical to the brain microcirculation and blood-brain barrier (BBB) integrity (Tran et al, 1996;Wang et al, 1997). In this respect, soluble TM-based therapeutics have been used to treat BBB-associated neurological disorders such as stroke (Wenzel et al, 2014). Moreover, elevated TM release or "shedding" into serum invariably accompanies the cerebrovascular endothelial activation typically associated with neurodegenerative disorders (Festoff et al, 2012), stroke (Hassan et al, 2003), cerebral small vessel disease (Giwa et al, 2012) and traumatic brain injury (Yokota et al, 2002).…”
Section: Introductionmentioning
confidence: 99%